THE EFFECTIVENESS OF PROJECT-BASED LEARNING AND PROBLEM-BASED LEARNING ON EFL TERTIARY LEVEL STUDENTS' WRITING ACHIEVEMENT - Affandi, Ahmad (2015)
The terms project-based learning (PjBL) and problem-based learning (PBL) are each used to describe a range of instructional strategies. The breadth of their respective definitions, their conceptual similarity, and the use of the shorthand term PBL result in some confusion in the literature (Donelly& Fitzmaurice, 2005).The present study was intended to examine the effectiveness of PjBL and PBL in teaching writing at tertiary level and how students perceive both methods applied in their teaching learning. 78 participants were assigned into two intact-groups where each consists of 39 students, one group was taught by using PjBL and another using PBL. Quasi experimental design was employed to answer (1) the effects of PjBL and PBL in students writing achievement; (2) whether there is significant difference of students writing achievement between those who are taught by using PjBL and PBL; (3) the students perception regarding PjBL and PBL. The findings and discussion revealed that (1) PjBL and PBL methods were able to improve the students writing result. This can be seen from the t value of PjBL group (t=-5.442, df. 38,p=.000) and PBL group (t=-2.619,df=38,p=.013) which were more than the alpha (.05); (2) there is no significant difference of students writing achievement between those who are taught by using PjBL and PBL (t=.527,df=76,p=.600). It might be due to the similarities of PjBL and PBL in terms of the classroom techniques for instance group discussion and peer-feedback and that the two methods focus on open ended tasks (Larmer, 2014); (3) students perceived those methods positively. They found the instruction was different from the teaching process they commonly had. PjBL enable them to think a contextual problem, work together in group, develop the critical thinking, and become more explorative. Similarly, it was also found that PBL made them engaged in the learning. Both methods help students to be able to identify the structure as well as develop their ideas for argumentative writing. In relation to the disadvantages, PjBL is a time-consuming process dealing with time allocation for making a project. However in PBL the challenges are on the exploration stage and group work. The group work is the strength and weakness of this method concurrently. Key Words: Project-based Learning (PjBL), Problem-based Learning (PBL), EFL Tertiary Level, Writing Achievement